A study on the impact of Kovach theory on motivation on the employees of Petronas Penapisan Terengganu Sdn. Bhd. / Siti Salha Dul Hadi - Dul Hadi, Siti Salha (Faculty of Administrative Science and Policy Studies, 2004)
Motivation is an inner desire to satisfy an unsatisfied need. From a business perspective, motivation is the willingness to achieve organizational objectives. Through the motivation process, employees go from need to motive to behavior to consequence to satisfaction or dissatisfaction. Managers have come to realize that a motivated and satisfied workforce can contribute powerfully to bottom-line of profits. In this study, I choose factors from Kovach theory on motivation to the employees at Petronas Penapisan Terengganu Sdn Bhd (PPTSB), Kertih, Kemaman. Kovach stated that good wages, interesting work, discipline oriented, job security, good working conditions, promotion and organization growth sympathetic help with personal problems are the factors that contribute to employees' motivation. Employees in PPTSB face challenging work because PPTSB is oil industries company that joint venture with other oil industry in other country. So that they have to have employees that give their full committed to their work. For the purpose of this study, descriptive research was deployed in order to identify factors that contribute to motivation. Judgmental and convenience sampling has been utilized with 60 respondents as the sample size. But it is only 54 feedbacks of respondents. Self-administered questionnaire was used as the survey instrument besides interviews as the sources of primary data. Other reliable resources also served as secondary data. By using the analysis generated by SPSS (a computerized statistical software), results are analyzed and deduction being drawn. Looking at the result in data analysis and cross tabulation did hypothesis testing.